Humanistic Learning Strategies in Building Students' Academic Ethics - M. Munif (Agrapana Media, 2026)
This study aims to analyze the implementation of humanistic learning strategies in fostering students’ academic ethics at the Bafa Kediri Institute of Islamic Studies. The research employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with lecturers and students, and documentation of academic activities. The findings indicate that the humanistic learning strategies implemented include personalized learning, the creation of psychologically safe learning environments, real-issue-based learning, digital-based reflective learning, collaborative learning, lecturers’ digital role modeling, and the integration of spiritual values into the learning process. These strategies were found to promote students’ academic ethical awareness, as reflected in increased honesty, responsibility, discipline, and mutual respect. The findings also suggest that the development of academic ethics is more effective when the learning process addresses students’ personal, social, and spiritual dimensions holistically. This study contributes a contextual and relevant humanistic learning model for strengthening academic culture in Islamic higher education institutions.